Use of low dose vaginal misoprostol in office hysteroscopy: a pre–post interventional study. (18th August 2021) - New, Erika P.; Sarkar, Papri; Mikhail, Emad; Plosker, Shayne; Imudia, Anthony N.
Abstract: A pre-post interventional study of patients undergoing office hysteroscopy alone and in combination with endometrial biopsy was performed during October 2015–March 2018 to evaluate the effect of low dose vaginal misoprostol on patient's pain. Pain scores were assessed using the visual analog scale at the completion of the procedure. There were 646 patients included in the study. Of these, 462 had office hysteroscopy alone; 206 (44.6%) received 50 mcg of vaginal misoprostol the night prior to the procedure and the remaining 256 (55.4%) patients had no cervical ripening. The reported pain score following hysteroscopy was significantly lower among patients who received misoprostol [4(0–10) vs. 5(0–10); p =.001]. Most patients (78.2%) did not report any misoprostol related side effects. Of the 184 patients who underwent a combination of office hysteroscopy and endometrial biopsy, 97 (52.7%) received pre-procedure vaginal misoprostol while 87 (47.3%) did not. Post procedure pain was independent of pre-treatment with vaginal misoprostol (6.3 ± 2.7 vs. 6.6 ± 2.7; p = .54). Impact statement: What is already known on this subject? Office hysteroscopy and endometrial biopsy is increasingly performed for evaluation of various gynaecologic conditions, however, patients' perceived pain at the time of procedure may lead to incomplete procedures. Various doses of misoprostol have been tested to reduce patients' pain, however none lower than 200 mcg vaginally, and at these doses, side effects are reported. What the results of this study add? To date, there is a scarcity of published data on the use of low dose misoprostol (50 mcg) in gynaecologic procedures. Our study found that the use of low dose vaginal misoprostol prior to office hysteroscopy is associated with lower reported pain and tenaculum utilisation during the procedure. However, vaginal misoprostol prior to successive office hysteroscopy and endometrial biopsy failed to decrease the reported pain, and the overall pain score was higher than hysteroscopy alone. What the implications are of these findings for clinical practice and/or further research? The use of low dose vaginal misoprostol (50 mcg) the evening prior to office hysteroscopy is associated with lower reported pain and tenaculum utilisation and is not associated with significant side effects. Therefore, 50 mcg of misoprostol could be used in clinical practice as a method to reduce patients' reported pain during office hysteroscopy.